Annie Secord’s “Personal Service”: The Role of Affluent Women in Edmonton’s Early Music Culture - Meyers-Riczu, Jamie (Intersections, 2022)
This article investigates the role of Annie York Secord, an affluent woman from Edmonton’s early settlement, in developing the community’s music culture. Her journals and appearances in local newspapers between 1890 and 1920 reveal the financial conditions and personal motivations that led her to foster musical culture through fundraising, attending concerts, supporting music education, and hosting events. This substantial work was often overlooked as “personal service,” contrasting the public city-building of Edmonton’s pioneering men. In studying Annie, this article acknowledges the contribution of wealthy women in cultivating musical culture in prairie settlements, the status-seeking that underlies these contributions, and the ethical questions behind the material conditions that allowed for the development of a music culture.